(untitled) (Mongolian Journal of International Affairs, 2015)
Mongolia’s outreach to Southeast Asia is part of a wider global strategy to raise its profi le in its own region and on the Eurasian continent. Mongolian policymakers now believe the nation needs tore-interpret its ‘third neighbor’ policy so that its voice is heard on Asian issues and not just wait on the sidelines for larger powers to make its decisions. Mongolia has adopted a very activist approach to elevate its political and economic ties to Southeast Asia in hopes of diversifying markets for its abundant minerals and animal by-products, purchasing consumer and high tech products from a wider range of partners, and attracting new types of FDI. It has re-invigorated past associations with nations that were part of Mongolia’s communist past such as Vietnam, Laos, and Cambodia, and, even more significantly, spent considerable effort to establish strong new relationships with major regional players such as Indonesia, Singapore, and Thailand. Mongolian Journal of International Affairs Vol.19 2014: 13-33